The Moderating Role of Financial Literacy in the Relationship between Market Sentiment, Social Media, and Generation Z’s Cryptocurrency Investment Decisions - Anugerah, Rheiza Marell; Nirawati, Lia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid expansion of cryptocurrency has captivated Generation Z, yet its high volatility means investment decisions are strongly influenced by market sentiment indicators like the Fear and Greed Index (FGI) and social media information. Limited financial literacy can intensify behavioral biases. This study examines the effects of FGI and social media on Generation Z’s cryptocurrency investment decisions, with financial literacy as a moderating variable. Using a quantitative approach, data were collected from 152 active cryptocurrency investors in the past six months via a Likert-scale questionnaire. Analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 (v.4.1.1.4). Results show that both FGI and social media have significant positive effects on investment decisions. Financial literacy has a direct positive effect and significantly moderates the influence of both FGI and social media, attenuating the impact of sentiment and online information by fostering more rational decision-making. These findings highlight the importance of improving financial literacy to reduce emotional bias and enhance the quality of Generation Z’s investment decisions in the cryptocurrency market.